CENDRO FISHING TECHNIQUE (Tylosurus crocodilus) USING GILLNET IN THE NUMBER OF PASIA NAN TIGO IN KOTO KOTO TANGAH KOTA PADANG WEST SUMATERA PROVINCE - Ahda Rahim Zirli; Bustari Bustari; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted at the end of June 2017 in Kelurahan Pasia Nan Tigo Padang City West Sumatera Province This study aims to determine the construction of gillnet its fishing techniques using gillnet. Observation method used in this research is the method of observation and interview. From the results of research on the construction of gillnet with mesh size 2 inches without bottom rope, sinker with shortening value 53% Using cendro fishing technique amount of catches weight (kg) that is 3581 kg for 49 times operation. Based on the length of fish cendro (cm) averaging 82 cm and the average body height of 6.8 cm. The main target of catching fish is cendro (Tylosurus crocodilus).Keywords: Fishing Engineering, Construction, Cendro Fish.